A new modification of 3 in 1 standing frame for children with cerebral palsy - Fatimahwati Hamzah,; Saiful Hasley Ramli,; Sazlina Kamaralzaman,; Rosalam Che Me,; Noraini Naseran,; Umawathy Techanamurthy, (Fakulti Kejuruteraan ,UKM,Bangi., 2023)
Standing Frame (SF) is commonly used in rehab training for children with cerebral palsy (CP), but the design regarding patients’ needs, conditions, and environments is rarely investigated. In this study, the researchers modified the standing frame by adding a controlling and monitoring system and included a 3 in 1 design that consisted of lying down, sitting, and standing postures. Six (6) volunteer respondents answered the questionnaire, and three (3) participants with CP were involved in this research to determine the usability of the modified 3 in 1 SF. The result of the questionnaire found that the 3 in 1 SF developed were interesting products, easy to use, safe, creative, and innovative products. Furniture Testing Laboratory results are: there are no fractures of any member, joint, or component, there is no loosening of joints intended to be rigid, seating fulfills its functions after removal of the best loads, and seating fulfills the stability requirement. Overall, 3 in 1 SF is well-developed, but a little bit of improvement is still needed for further research. Hopefully, the 3 in 1 SF will help the children with CP develop self-reliance and assist them in their everyday activities at home and school.